Dialog Ritus Ma’pealloam Dalam Makna Mutualitas Aluk dan Kekristenan Menggunakan Persfektif Paul Tillich - Prionaray Bram M (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Through this research, we will then examine in depth how basically the problems that arise are due to the lack of dialogue that occurs between Christianity and aluk, when discussing the capacity of ma'pealloam. Many who appear in church circles, try to see that they are basically adopting aluk ideology. This is what is then attempted to be dialogued with Paul Tillich's mutualist concept, to look further into the aims and objectives of this matter. The research method used is a qualitative research method, with an anthropological approach. This will then facilitate the ability to see cultural history and enable responses from within the awareness of what has been experienced up to now. Through the results of this research, it was found that basically the church took over the decision to follow the ma'pealloam schedule, to enable maintaining unity between aluk and existing Christianity.